1996
DOI: 10.1152/ajpgi.1996.271.3.g494
|View full text |Cite
|
Sign up to set email alerts
|

Acute alcohol produces hypoxia directly in rat liver tissue in vivo: role of Kupffer cells

Abstract: Previous studies using liver slices and isolated perfused rat liver have suggested that ethanol causes hypoxia by increasing oxygen consumption. However, ethanol also increases blood flow to the liver, a phenomenon that may counteract the effects of hypermetabolism by increasing oxygen delivery. Thus whether ethanol causes hypoxia in vivo remains unclear. To clarify this important point, female Sprague-Dawley rats (100-125 g) simultaneously received pimonidazole (120 mg/kg ip), a 2-nitroimidazole hypoxia marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
73
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 0 publications
6
73
0
1
Order By: Relevance
“…Recently, it was reported that high doses of ethanol impair hepatic microcirculation (19) by producing endothelin-1, (20) and we recently detected hypoxia directly in rats on the Tsukamoto-French protocol (21) and in the perfused liver after acute exposure to ethanol in vivo (22). These findings support the idea that hypoxia directly contributes to alcohol-induced liver injury.…”
Section: Hypoxiasupporting
confidence: 86%
“…Recently, it was reported that high doses of ethanol impair hepatic microcirculation (19) by producing endothelin-1, (20) and we recently detected hypoxia directly in rats on the Tsukamoto-French protocol (21) and in the perfused liver after acute exposure to ethanol in vivo (22). These findings support the idea that hypoxia directly contributes to alcohol-induced liver injury.…”
Section: Hypoxiasupporting
confidence: 86%
“…This may also have the effect of changing oxygen gradients in tissues. Indeed, this is precisely the series of events that we propose occurs with NO in alcohol hepatotoxicity [49] , which has been shown to be associated with tissue hypoxia [53,54] . Several studies have clearly demonstrated that acute alcohol exposure "steepens" the hepatic oxygen gradient as a consequence of ethanol oxidation [55,56] , thus rendering the pericentral regions of the liver lobule hypoxic [53] .…”
Section: Production In Complexⅰ(c) O2 •-Dismutation To Hydrogen Peromentioning
confidence: 73%
“…Indeed, this is precisely the series of events that we propose occurs with NO in alcohol hepatotoxicity [49] , which has been shown to be associated with tissue hypoxia [53,54] . Several studies have clearly demonstrated that acute alcohol exposure "steepens" the hepatic oxygen gradient as a consequence of ethanol oxidation [55,56] , thus rendering the pericentral regions of the liver lobule hypoxic [53] . Thus, the effect of acute hypoxia in an individual actively drinking is proposed to be exaggerated in the chronic alcohol consumer as a consequence of the alcohol dependent increase in inhibition of mitochondrial respiration by NO [14] .…”
Section: Production In Complexⅰ(c) O2 •-Dismutation To Hydrogen Peromentioning
confidence: 73%
“…Apoptotic cells were assessed morphologically by identifying Gene Therapy condensed and fragmented nuclei from 2000 cells in H& E slides using methods described elsewhere, 42 and areas in sections stained for collagens by Sirius red F2BA or trichrome were quantified by image analysis. 43 An Image-1/AT image acquisition and analysis system (Universal Imaging, Chester, PA, USA) incorporating an Axioskop 50 microscope (Carl Zeiss, Thornwood, NY, USA) was used to capture and analyze Sirius red-and trichrome-stained tissue sections at ×40 magnification. Detection thresholds were set for the appropriate color of stained collagen based on an intensely labeled point and a default color threshold range was assigned.…”
Section: Clinical Chemistry and Histologymentioning
confidence: 99%